Bridging the age gap in breast cancer: impact of omission of breast cancer surgery in older women with oestrogen receptor-positive early breast cancer on quality-of-life outcomes. Issue 3 (24th March 2021) - Morgan, J L; Shrestha, A; Reed, M W R; Herbert, E; Bradburn, M; Walters, S J; Martin, C; Collins, K; Ward, S; Holmes, G; Burton, M; Lifford, K; et al.
Abstract: Background: Primary endocrine therapy may be an alternative treatment for less fit women with oestrogen receptor (ER)-positive breast cancer. This study compared quality-of-life (QoL) outcomes in older women treated with surgery or primary endocrine therapy. Methods: This was a multicentre, prospective, observational cohort study of surgery or primary endocrine therapy in women aged over 70 years with operable breast cancer. QoL was assessed using European Organisation for Research and Treatment of cancer QoL questionnaires QLQ-C30, -BR23, and -ELD14, and the EuroQol Five Dimensions 5L score at baseline, 6 weeks, and 6, 12, 18, and 24 months. Propensity score matching was used to adjust for baseline variation in health, fitness, and tumour stage. Results: The study recruited 3416 women (median age 77 (range 69–102) years) from 56 breast units. Of these, 2979 (87.2 per cent) had ER-positive breast cancer; 2354 women had surgery and 500 received primary endocrine therapy (125 were excluded from analysis due to inadequate data or non-standard therapy). Median follow-up was 52 months. The primary endocrine therapy group was older and less fit. Baseline QoL differed between the groups; the mean(s.d.) QLQ-C30 global health status score was 66.2(21.1) in patients who received primary endocrine therapy versus 77.1(17.8) among those who had surgery plus endocrine therapy. In the unmatched analysis, changes in QoL between 6 weeks and baseline were noted in several domains, but by 24 months most scores had returned to baseline levels. In the matched analysis, major surgery (mastectomy or axillary clearance) had a more pronounced adverse impact than primary endocrine therapy in several domains. Conclusion: Adverse effects on QoL are seen in the first few months after surgery, but by 24 months these have largely resolved. Women considering surgery should be informed of these effects. Abstract : The Age Gap study is a multicentre, prospective, observational cohort study that recruited 3416 older women aged over 70 years with operable breast cancer. The present study compared quality-of-life outcomes in older women treated with surgery or primary endocrine therapy for breast cancer. Adverse effects on quality of life were seen in the first few months after surgery, but by 24 months had largely resolved. Women considering surgery should be informed of these effects. Both surgery and PET affect QoL negatively The Bridging the Age Gap study is a multicentre, prospective, observational cohort study that recruited 3416 older women age >70 with operable breast cancer. This study compared quality-of-life outcomes in older women treated with surgery or PET for breast cancer and shows that adverse effects on quality-of-life are seen in the first few months after surgery but by 24 months these have largely resolved. Women considering surgery should be informed of these impacts.